2009
DOI: 10.2175/106143009x407456
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Hexavalent Chromium from Aqueous Solution on Raw and Modified Activated Carbon

Abstract: Hexavalent chromium [Cr(VI)] is toxic and readily adsorbed by some adsorbents; therefore, its removal from wastewater is extremely important. Batch adsorption of Cr(VI) from aqueous solution using raw and acid-modified activated carbon was investigated in this study. The Cr(VI) sorption was found to be dependent on pH, contact time, initial concentration of solution, adsorbent dose, and temperature. The maximum efficiencies of Cr(VI) removal were 97.67 and 99.87% for activated carbon (AC 0 ) and modified activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…(7), it is observed that the percentage removal of Chromium increases by increasing the temperature from 30 to 70 o C for all materials. This increase is due to the increase of the rate of adsorption at higher temperature which indicates that the adsorption process is endothermic (50). The optimum removal was for sawdust at 70 o C by 82% followed 80.7% for banana waste at 60 o C. Similar results were reported by (20), (6) and (27).…”
Section: Effect Of Temperature On Cr Adsorptionsupporting
confidence: 82%
“…(7), it is observed that the percentage removal of Chromium increases by increasing the temperature from 30 to 70 o C for all materials. This increase is due to the increase of the rate of adsorption at higher temperature which indicates that the adsorption process is endothermic (50). The optimum removal was for sawdust at 70 o C by 82% followed 80.7% for banana waste at 60 o C. Similar results were reported by (20), (6) and (27).…”
Section: Effect Of Temperature On Cr Adsorptionsupporting
confidence: 82%
“…Adsorption Isotherms for the Mulberry Branch Biomass Char with Adsorption of Copper(II) Acetate [Cu(II)]. Adsorption isotherms are important for describing how an adsorbate will interact with an adsorbent, and are critical in optimizing the use of adsorbents (Tang et al, 2009). As the results described in section 3.3 show, copper(II) acetate [Cu(II)] was selected to investigate the adsorption isotherms.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, epidemiological evidence-such as a high incidence of cancer among coppersmiths-suggests a primary carcinogenic role for copper (Ho et al, 2002;Larous et al, 2005;Rao et al, 2006). Another important toxic heavy metal, chromium, has been recognized as one of the most serious pollutants among heavy metals for its toxic effects, nonbiochemical degradation characteristics, and accumulation throughout the food chain (Tang et al, 2009). Copper, in a natural state, exists in two most common and stable oxidation states-trivalent chromium [Cr(III)] and hexavalent chromium [Cr(VI)].…”
Section: Introductionmentioning
confidence: 99%
“…Their findings revealed that the adsorption of Cr(VI) decreased as pH increased, with the maximum adsorption occurring at pH 2. 149 In another study, when the pH was increased from 2 to 6, the adsorption capacities of Cu(II) increased from 0.7 mg/g to 1.76 mg/g. Another crucial element in the adsorption process is the particle size.…”
Section: Heavy Metal Removalmentioning
confidence: 95%